Focused Leadership Influencing the Development, Effectiveness and Sustainability of Professional Learning Communities: Evidence from TVET Institutions in Cambodia - Chamnan Sok; Kosal Thay; Sovantha Ros; Phyny Sin; Tonghor Hab; Sarom Mok (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Although Professional Learning Communities (PLCs) have been widely touted as a way to enhance student learning and instructional practice, many PLCs have failed to attain sustained effectiveness because of inconsistent or distracted leadership. This concurrent mixed-methods study looked at how focused, purpose-driven leadership affected the sustainability and efficacy of PLCs in Cambodian TVET Institutions. The study examined how leadership behaviors pertaining to clarity, cooperation, structural support, and trust affected PLC practices and educational efficacy under the guidance of transformational leadership theory. A researcher-developed Likert-scale survey measuring leadership behaviors, PLC effectiveness, collective efficacy, and organizational conditions was used to gather quantitative data from 150 teachers. In order to investigate lived experiences with leadership behaviors in PLC contexts, semi-structured interviews with twenty educators—including teachers, instructional coaches, PLC leads, department chairs, and administrators—were used to collect qualitative data. Strong positive correlations between focused leadership behaviors and PLC effectiveness were found through quantitative analyses, especially in the areas of goal clarity, accountability, trust-building, and structural support. Four themes emerged from the qualitative analysis: (1) clarity and direction are established by focused leadership; (2) collaboration quality is directly impacted by leadership activities; (3) PLC sustainability is shaped by time and structural support; and (4) effective PLCs require a foundation of relational trust. Relational trust emerged as a crucial mechanism promoting long-term collaboration and collective efficacy, and integrated findings showed convergence around the significance of clarity, consistency, and intentional leadership behaviors. The results provide useful implications for school administrators looking to enhance collaborative practice and instructional coherence. They indicate that focused, transformational leadership enhances PLC functioning and professional learning outcomes. The results were meant to guide leadership development initiatives and provide school administrators with practical tactics for creating strong, well-functioning professional communities that promote the achievement of both teachers and students.